The mapping of the quasi-two-dimensional Fermi surface sections of organic conductors - Hayes, W; Nam, MS; Symington, J; Blundell, S; Ardavan, A; Singleton, J (2001)
We have developed a model for parameterizing the shape of the quasi-two-dimensional (Q2D) Fermi surface (FS) sections found in many organic molecular metals. Using this model, we show that it is possible to extract more detail about the Q2D pocket shape from angle-dependent magnetoresistance oscillations than in the traditional approximation which assumes an elliptical FS shape. We also consider the implications for cyclotron resonance experiments.